From Service Design to Social Governance: Extending Design Thinking into Public Service - Zhang, Muzi (International Journal of Social Sciences and Public Administration, 2026)
Design thinking is widely applied at various locations for problem-solving; it has gradually become a routine way of work among governments, NGOs and others to improve services or resolve complex social issues by means of orderly arrangement. Based on this paper, how Design Thinking is migrating from Service Design to Governance in general Social, What the Theoretical Foundation for such a transition Is and How it shapes Public Sector Practice through Human-centred approach. Based on international case studies and governance theories, the paper will identify the enabling Conditions and structural hindrances to this Process. Situate design thinking within the framework of participatory governance to explore its applicability in promoting reforms of the public sector across different nations. Based on the above analysis, Design Thinking provides a reasonable Pathway for Citizen Engagement and Policy Iteration among multiple agencies; Its introduction to Governance is not as straightforward as it seems.